2021
DOI: 10.3390/s21196465
|View full text |Cite
|
Sign up to set email alerts
|

Terahertz Imaging for Breast Cancer Detection

Abstract: Terahertz (THz) imaging has the potential to detect breast tumors during breast-conserving surgery accurately. Over the past decade, many research groups have extensively studied THz imaging and spectroscopy techniques for identifying breast tumors. This manuscript presents the recent development of THz imaging techniques for breast cancer detection. The dielectric properties of breast tissues in the THz range, THz imaging and spectroscopy systems, THz radiation sources, and THz breast imaging studies are disc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(33 citation statements)
references
References 90 publications
0
19
0
Order By: Relevance
“…Among them, the technology based on terahertz (THz) frequency waves is gaining popularity as a powerful nondestructive sensing tool owing to its unique capabilities of high transparency for soft materials and resonant response with intermolecular vibration [ 6–8 ]. Various studies have been conducted on the practical use of THz sensing, including material science [ 9–12 ], component fabrication (such as emitters and detectors) [ 13–15 ], system development [ 16 , 17 ], and sensing applications [ 18 , 19 ]. In the case of component fabrication, the challenge is to create a structure that efficiently couples with a THz wave, having a rapid cycle time of sub-picoseconds and small photon energy amounting to several meV.…”
Section: Introductionmentioning
confidence: 99%
“…Among them, the technology based on terahertz (THz) frequency waves is gaining popularity as a powerful nondestructive sensing tool owing to its unique capabilities of high transparency for soft materials and resonant response with intermolecular vibration [ 6–8 ]. Various studies have been conducted on the practical use of THz sensing, including material science [ 9–12 ], component fabrication (such as emitters and detectors) [ 13–15 ], system development [ 16 , 17 ], and sensing applications [ 18 , 19 ]. In the case of component fabrication, the challenge is to create a structure that efficiently couples with a THz wave, having a rapid cycle time of sub-picoseconds and small photon energy amounting to several meV.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, methods used to determine the extent of tumor resection have inherent limitations. [27][28][29] However, THI offers a promising solution to identify the extent of tumor resection and metastatic SNLs during surgery and reduce the number of reoperations. Fitzgerald was the first researcher who detected breast tumors by THI and determined the exact location and shape of the tumor by imaging terahertz and showed that THI could distinguish healthy and cancerous breast tissues.…”
Section: Breast Cancermentioning
confidence: 99%
“…The recent developments in THz imaging technology and its application for breast tumor identification is reported by Wang ( 2021 ) and exploited the potential application of THz imaging and spectroscopy systems for breast cancer detection, with a discussion of the breast tissue’s dielectric properties within THz range, THz radiation sources, and imaging with spectroscopy. The methods for improvement of data collection, processing and resolution based on chemometrics are summarized.…”
Section: Introductionmentioning
confidence: 99%